Pengaruh Self-Efficacy, Minat Belajar, dan Lingkungan Keluarga Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi: The Influence of Self-Efficacy, Learning Interest, and Family Environment on Learning Outcomes in the Economics Subject - Saputri, Mila; Sadiah, Ati; Nurdianti, Raden Roro Suci (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The problem addressed in this study is the low learning outcomes of students in the Economics subject at State Senior High School 6 Tasikmalaya, indicated by the large number of students who have not met the Learning Objectives Achievement Criteria (KKTP). This low achievement is apparent across various learning outcome indicators, including intellectual skills, cognitive strategies, attitudes, and motor skills, which have not been optimally developed. This phenomenon prompted an investigation into the factors influencing learning outcomes, encompassing both internal aspects, such as self-efficacy and learning interest, and external aspects, like the family environment. This study aimed to determine the partial and simultaneous influence of self-efficacy, learning interest, and family environment on the learning outcomes of eleventh-grade students in Economics. The study employed a quantitative approach with a survey method using a questionnaire. The sample consisted of 118 students selected through a saturated sampling technique. Data analysis was conducted using multiple linear regression via SPSS version 25. The results showed that self-efficacy significantly influences learning outcomes, learning interest significantly influences learning outcomes, and the family environment also significantly influences learning outcomes. Simultaneously, these three variables have a significant effect on learning outcomes, with an R-Square value of 0.667. This indicates that their combined contribution accounts for 66.7% of the learning outcomes, while the remaining 33.3% is influenced by other factors not examined in this research.